(untitled) (Cultoure: Jurnal Ilmiah Pariwisata Budaya Hindu, 2025)
Community-based tourism village development is a crucial strategy for enhancing local welfare and cultural preservation, in line with the mandate of national tourism policy. Nevertheless, its implementation often faces fundamental challenges, such as low active community participation, minimal socialization, and a lack of synchronization among stakeholders. Kampung Lawas Maspati in Surabaya, a tourist attraction with historical potential, experiences similar obstacles in optimally coordinating resident participation, indicating weaknesses in managerial functions. This study aims to analyze the implementation of the actuating function based on the POAC management framework in Kampung Lawas Maspati, Surabaya, and to identify its supporting and inhibiting factors. The method used is descriptive qualitative with a case study design. Data was collected through in-depth interviews, participatory observation, and documentation, which were then analyzed using the Miles and Huberman interactive model. The results show that the implementation of tourism activities runs effectively thanks to a collective strength sustained by the spirit of mutual cooperation. Resident motivation is successfully built through a combination of financial incentives (transparent fee distribution and "saweran" bonuses) and non-financial incentives (a sense of pride and togetherness). Participatory leadership that sets an example, flexible two-way communication via WhatsApp groups, and an adaptive directing system are key to its success. However, several challenges were identified, such as the absence of written Standard Operating Procedures (SOPs), which risks service inconsistency, and limited human resource capacity for professional services. Therefore, the development of SOPs and human resource capacity building are the main recommendations for sustainability. Keywords: Tourism Village Management, Community Participation, POAC Management, Actuating, Kampung Lawas Maspati